2013
DOI: 10.1089/ars.2012.4997
|View full text |Cite
|
Sign up to set email alerts
|

Human GGT2 Does Not Autocleave into a Functional Enzyme: A Cautionary Tale for Interpretation of Microarray Data on Redox Signaling

Abstract: Aims: Human c-glutamyltranspeptidase 1 (hGGT1) is a cell-surface enzyme that is a regulator of redox adaptation and drug resistance due to its glutathionase activity. The human GGT2 gene encodes a protein that is 94% identical to the amino-acid sequence of hGGT1. Transcriptional profiling analyses in a series of recent publications have implicated the hGGT2 enzyme as a modulator of disease processes. However, hGGT2 has never been shown to encode a protein with enzymatic activity. The aim of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…Perhaps, some role may play a chemokine-like CX3C motif contained in the GGT molecule [33] or exogenous GGT might mimick cytokine-like activities of GGT-related proteins produced by genes different from the GGT1 [34]. For example, the GGT2 gene located close to the GGT1 chromosomal region seems to encode for a full length, enzymatically inactive protein, not localized to the plasma membrane [35] and, according to some Authors, involved in redox modulation [36]. It might also be possible to envisage protein-protein interactions leading to the expression of other procoagulant cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, some role may play a chemokine-like CX3C motif contained in the GGT molecule [33] or exogenous GGT might mimick cytokine-like activities of GGT-related proteins produced by genes different from the GGT1 [34]. For example, the GGT2 gene located close to the GGT1 chromosomal region seems to encode for a full length, enzymatically inactive protein, not localized to the plasma membrane [35] and, according to some Authors, involved in redox modulation [36]. It might also be possible to envisage protein-protein interactions leading to the expression of other procoagulant cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…GGT2 mRNA has been detected and this has led to the assumption that GGT2 encodes an enzymatically active protein (Auman et al, 2008; Moon et al, 2012). However, we have recently shown that GGT2 propeptides encoded by all three isoforms of GGT2 failed to autocleave, were enzymatically inactive, did not localize to the plasma membrane, and were rapidly degraded within the cell (West, Wickham, Parks, Sherry, & Hanigan, 2013). …”
Section: Function Of Ggtmentioning
confidence: 99%
“…GGT1) and GGT2, and 94% amino acid identity. The GGT2 gene is transcribed and GGT2 protein has been detected, but the protein has no enzymatic activity and is rapidly degraded within the cell (West, Wickham, et al, 2013). Some microarray platforms have probes that distinguish between GGT1 and GGT2, while others do not creating confusion as to which mRNA is being measured.…”
Section: Redox Regulation Of Ggtmentioning
confidence: 99%
“…It was fully intact in the 4GG2 model of hGGT1, but it was a mix of intact and broken bonds in the 4DGX model, perhaps attributable to x-ray radiation damage. Site-directed mutagenesis studies with rat and human GGT1 demonstrated that both disulfide bonds are critical for optimal autocleavage of mammalian GGT1 into active heterodimers (36,38,39). The formation of the Cys-50/Cys-74 and Cys-192/Cys-196 disulfide bridges may contribute to the proper folding of hGGT1 and, thereby, facilitate autocleavage into the activated heterodimer.…”
Section: Table 1 Data Collection and Refinement Statisticsmentioning
confidence: 99%
“…The bacterial GGTs with crystal structures lack N-glycosylation, yet their propeptides are properly folded and undergo autocleavage (27)(28)(29)37). Two cysteines (Cys-50 and Cys-74) are conserved in the large subunit of all eukaryotic GGT1s and are required for efficient autocleavage of hGGT1 (38,39). Both of these sites are alanines in the bacterial GGTs.…”
mentioning
confidence: 99%